Mycobacterium marinum Infection After Exposure to Coal Mine Water. (17th December 2015) - Huaman, Moises A.; Ribes, Julie A.; Lohr, Kristine M.; Evans, Martin E.
Abstract: Mycobacterium marinum infection has been historically associated with exposure to aquariums, swimming pools, fish, or other marine fauna. We present a case of M marinum left wrist tenosynovitis and elbow bursitis associated with a puncture injury and exposure to coal mine water in Illinois.